PENGGUNAAN VIDEO ANIMASI BERBASIS PROYEK DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA SMA - Arisfa, Nurul; Muhammad, Muhammad; Muzana, Syarifah Rahmiza; Bukhari, Bukhari; Hasbullah, Hasbullah (Jurnal Dedikasi Pendidikan, 2025)
This research aims to improve problem solving abilities using project-based animated videos at SMA Negeri 1 Kuta Baro. Sampling in this research used a saturated sampling technique with the research sample consisting of 20 class XI Science students. This research uses the Research and Development (R&D) development method with a 4D model. Data on problem solving abilities was collected through tests in the form of essay questions.Analysis of problem solving abilities was tested statistically, namely the N-Gain test, and hypothesis testing using the Paired Sample T-Test. The results of research on problem solving abilities obtained an average pre-test score (57.7) and post-test (86.05) with an average N-Gain of 0.67 in the medium category. The results of hypothesis testing in the Paired Sample T-Test obtained a sig value. (2-tailed) of 0.000 < 0.05, thus these results state that hypothesis testing in the research shows that Ha is accepted and Ho is rejected. The conclusion of the research is that the use of project-based animated videos can improve the problem-solving abilities of class XI Science students at SMAN 1 Kuta Baro on Sound Waves material.